Humanizing childhood in early twentieth century Spain - Ribagorda, Álvaro (Historia y Memoria de la Educación, 2022)
Review of the book ANNA KATHRYN KENDRICK, Humanizing childhood in early twentieth century Spain. Cambridge: Legenda, 2020